Electrochemical behavior and corrosion resistance of Ti-15Mo alloy in naturally-aerated solutions, containing chloride and fluoride ions - Rodrigues, A. V. [UNESP]; Oliveira, N. T. C. [UNESP]; Santos, M. L. dos [UNESP]; Guastaldi, A. C. [UNESP] (Springer, 2015)
The electrochemical behavior and corrosion resistance of Ti-15Mo alloy to applications as biomaterials in solutions 0.15 mol L-1 Ringer, 0.15 mol L-1 Ringer plus 0.036 mol L-1 NaF and 0.036 mol L-1 NaF (containing 1,500 ppm of fluoride ions, F-) were investigated using open-circuit potential, cyclic voltammetry, and electrochemical impedance spectroscopy techniques, X-ray photoelectron spectroscopy and scanning electron microscope. Corrosion resistance and electrochemical stability of the Ti-15Mo alloy decreased in solutions containing F- ions. In all cases, there were formation and growth of TiO2 and MoO3 (a protector film), not being observed pitting corrosion, which might enable Ti-15Mo alloys to be used as biomedical implant, at least in the studied conditions, since the electrochemical stability and corrosion resistance of the passive films formed are necessary conditions for osseointegration.